Testing the ability of the ExoMars 2018 payload to document geological context and potential habitability on Mars. (April 2015) - Bost, N.; Ramboz, C.; LeBreton, N.; Foucher, F.; Lopez-Reyes, G.; De Angelis, S.; Josset, M.; Venegas, G.; Sanz-Arranz, A.; Rull, F.; Medina, J.; Josset, J.-L.; et al.
Abstract: The future ExoMars rover mission (ESA/Roscosmos), to be launched in 2018, will investigate the habitability of the Martian surface and near subsurface, and search for traces of past life in the form of textural biosignatures and organic molecules. In support of this mission, a selection of relevant Mars analogue materials has been characterised and stored in the International Space Analogue Rockstore (ISAR), hosted in Orléans, France. Two ISAR samples were analysed by prototypes of the ExoMars rover instruments used for petrographic study. The objective was to determine whether a full interpretation of the rocks could be achieved on the basis of the data obtained by the ExoMars visible-IR imager and spectrometer (MicrOmega), the close-up imager (CLUPI), the drill infrared spectrometer (Ma_Miss) and the Raman spectrometer (RLS), first separately then in their entirety. In order to not influence the initial instrumental interpretation, the samples were sent to the different teams without any additional information. This first step was called the "Blind Test" phase. The data obtained by the instruments were then complemented with photography of the relevant outcrops (as would be available during the ExoMars mission) before being presented to two geologists tasked with the interpretation. The context data and photography of the outcrops and of the samples were sufficient for the geologists to identify the rocks. This initial identification was crucial for the subsequent, iterative interpretation of the spectroscopic data. The data from the different spectrometers was, thus, cross-calibrated against the photographic interpretations and against each other. In this way, important mineralogical details, such as evidence of aqueous alteration of the rocks, provided relevant information concerning potential habitable conditions. The final conclusion from this test is that, when processed together, the ExoMars payload instruments produce complementary data allowing reliable interpretation of the geological context and potential for habitable environments. This background information is fundamental for the analysis and interpretation of organics in the processed Martian rocks. Highlights: First test of the ExoMars payload. Test with will characterised Mars analogue samples. Collaborative exercise with different ExoMars teams. Proposed protocol to increase the scientific return of the ExoMars mission.